RANCANG BANGUN KARYA SENI POLA UBIN MODEL FRAKTAL DARI POLA DUA DAN TIGA GARIS GENERIK DENGAN TEKNIK REFLEKSI HORIZONTAL-VERTIKAL DAN DIAGONAL - Tedjo Darmanto; Rizal Sopandi; Herdi Yunirwan (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
This research is done based on the needs of designing artworks that are easy to do through computer programs. The method used is a development method with two stages, namely the stage of duplication of generic data code and the stage of horizontal-vertical and diagonal reflection of images obtained from phase one to produce symmetrical images in subsequent phases. Tile pattern symmetrical drawing artwork can be designed and constructed with fractal models through generic two- and three-line patterns. The self-similarity properties of generic fractal objects can be duplicated through the reflection of horizontal-vertical and diagonal directions. Tile pattern artwork can be built in several phases with horizontal-vertical and diagonal mirroring before coloring. This tile pattern artwork is a visualization of object data in the form of recyclable Affine coefficients.